2021
DOI: 10.33043/jsacp.13.1.2-22
|View full text |Cite
|
Sign up to set email alerts
|

Description and Pilot Evaluation of a Dreamer Ally Training for Higher Education Staff and Faculty

Abstract: We describe a Dreamer Ally training provided to staff and faculty on a university campus and present results of a pilot evaluation of this training. The Dreamer Ally training was designed to (a) increase university faculty and staff awareness, understanding, and self-efficacy for working with Dreamer students and (b) stimulate action to make the campus more responsive to the challenges and contributions of Dreamer students. For the purpose of this study we define Dreamer students as inclusive of undocumented s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…While our context suggests that there are some policies and resources in place, the facilitation of the training sessions and our analysis of the survey responses demonstrates the clear need for investment in dedicated staffing, student groups, and physical space. Our findings build on the important work which has demonstrated the effectiveness of undocumented student support centers (Cisneros & Valdivia, 2020; Cisneros et al., 2022) and trainings to educate members of higher education communities about supporting undocumented students (Cisernos & Cadenas, 2017; Cisneros & Lopez, 2020; McWhirter et al, 2021). Specifically, our findings suggest that while the trainings were an effective tool for awareness and education, they also catalyze an understanding for the need for accountability of greater investment toward the success of all students regardless of immigration status.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…While our context suggests that there are some policies and resources in place, the facilitation of the training sessions and our analysis of the survey responses demonstrates the clear need for investment in dedicated staffing, student groups, and physical space. Our findings build on the important work which has demonstrated the effectiveness of undocumented student support centers (Cisneros & Valdivia, 2020; Cisneros et al., 2022) and trainings to educate members of higher education communities about supporting undocumented students (Cisernos & Cadenas, 2017; Cisneros & Lopez, 2020; McWhirter et al, 2021). Specifically, our findings suggest that while the trainings were an effective tool for awareness and education, they also catalyze an understanding for the need for accountability of greater investment toward the success of all students regardless of immigration status.…”
Section: Discussionsupporting
confidence: 67%
“…Similar trainings have been implemented at universities across the country and often focus on training faculty and staff to become knowledgeable and active allies for undocumented students in their communities. Evaluative studies demonstrate participants often sought to attend to learn more about this population and how to support undocumented students (McWhirter et al, 2021). In fact, these same studies found that UndocuAlly training led to faculty and staff working more closely together on broader institutional changes.…”
Section: Relevant Literaturementioning
confidence: 99%
“…This finding offers public administration and social services educators some direction in terms of their role in mentoring naturalized first-generation citizen students and the children of immigrants. Increasing the awareness of the opportunities for public service internships and possible careers, and providing education on the role of the individual in actively representing the interests of clientele through the lens of identity and shared heritage would seem to be important elements of an informed public administration curriculum and social services training (see McWhirter et al, 2021; Peters et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Vocational psychologists may deliver programmatic interventions, such as career education programs, that center on social-action projects that address community issues (Cadenas et al, 2020; McWhirter et al, 2021a, 2021b). Vocational psychologists can promote structural change and foster CC within institutions and as part of larger systems (e.g., education, healthcare, law, workforce), and advocate with and on behalf of clients, students, and communities that are impacted by social oppression in their career development.…”
Section: Critical Consciousness In the Future Of Vocational Psycholog...mentioning
confidence: 99%